2016
DOI: 10.1016/j.ebiom.2015.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization and Distribution of Rubella Antigen in Fatal Congenital Rubella Syndrome

Abstract: BackgroundAn estimated 100,000 cases of congenital rubella syndrome (CRS) occur worldwide each year. The reported mortality rate for infants with CRS is up to 33%. The cellular mechanisms responsible for the multiple congenital defects in CRS are presently unknown. Here we identify cell types positive for rubella virus (RV) in CRS infants.MethodsCells and organs involved in RV replication were identified in paraffin-embedded autopsy tissues from three fatal case-patients by histopathologic examination and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 39 publications
(45 reference statements)
4
41
0
Order By: Relevance
“…We also noticed that in all microcephaly cases that were positive by tissue RT-PCR, maternal symptom onset occurred during the first trimester, which might suggest that the virus can cause abnormal brain development when infection occurs early in organogenesis. Previous studies of rubella reported that the risk for fetal infection with congenital anomalies is highest when exposure/infection occurred before 11–12 weeks of gestation and sharply decreased with increasing gestational age ( 32 ) . …”
Section: Discussionmentioning
confidence: 99%
“…We also noticed that in all microcephaly cases that were positive by tissue RT-PCR, maternal symptom onset occurred during the first trimester, which might suggest that the virus can cause abnormal brain development when infection occurs early in organogenesis. Previous studies of rubella reported that the risk for fetal infection with congenital anomalies is highest when exposure/infection occurred before 11–12 weeks of gestation and sharply decreased with increasing gestational age ( 32 ) . …”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic, toxic, iatrogenic, and other noninfectious causes, congenital malformations can be caused by the vertical transmission of viruses, bacteria, and parasites such as cytomegalovirus, herpes simplex virus, rubella virus, Toxoplasma gondii, and Treponema pallidum. [15][16][17][18][19] Infection during the fi rst trimester of pregnancy is of particular concern with most of these agents and can be associated with serious consequences. On the other hand, cytomegalovirus infection at any point during pregnancy can result in severe CNS sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Rubella virus antigens were detected in myocardial fibroblasts of two patients, although they did not have histological signs of myocarditis or viral antigens in their cardiac myocytes (10). Additional evidence of the presence of viral antigens in adventitial fibroblasts of large blood vessels helps explain the possible mechanisms for congenital cardiovascular malformations (patent ductus arteriosus and branch pulmonary artery stenosis) in CRS patients.…”
Section: Introductionmentioning
confidence: 99%